2018
DOI: 10.1016/j.apenergy.2018.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of experimental studies of methane hydrate formation in a sandy porous medium

Abstract: Highlights • MH formation via excess-water method was numerically analyzed using T+H v1.5. • MH formation is determined as a kinetic reaction with dominant thermal processes controlling MH formation. • Flow, thermal, and kinetic rate parameters are optimized using a historymatching technique. • The spatial distributions of various phases at the end of the MH formation are strongly heterogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 102 publications
(115 reference statements)
1
72
0
Order By: Relevance
“…The pressure changes in the equilibrium model matched relatively well with those in the experiment. However, Yin et al (Yin, Moridis, Chong, et al, ; Yin, Moridis, Tan, & Linga, ) found that the Kinetic model is highly reliable to determine temperature changes and productivity. For future work, it will be necessary to identify changes in critical gas hydrate saturation using the equilibrium and kinetic models.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure changes in the equilibrium model matched relatively well with those in the experiment. However, Yin et al (Yin, Moridis, Chong, et al, ; Yin, Moridis, Tan, & Linga, ) found that the Kinetic model is highly reliable to determine temperature changes and productivity. For future work, it will be necessary to identify changes in critical gas hydrate saturation using the equilibrium and kinetic models.…”
Section: Discussionmentioning
confidence: 99%
“…The numerical studies of Yin et al [33,34] analysed through history-matching (inverse modelling) laboratory data of MH formation and dissociation in a sandy core in a 1.0 L reactor, and the optimized parameters determined in the process closely matched the pressure and temperature measurements and yielded consistent predictions of heterogeneous spatial distributions of all phases. The MH formation method of Chong et al [23,35] that provided the data for the Yin et al [33,34] studies was shown to lead to significantly heterogeneous spatial distributions of SH (high SH near the reactor cooling boundary, and low SH at the reactor centre) as a result of the apparatus design. The numerical studies of Yin et al [33,34] also determined that the thermal processes associated with the reactor cooling and the warm water injection (to effect dissociation) had a considerable impact on the spatial distribution of SH in the hydrate-bearing core, as did the ambient air temperature.…”
Section: Introductionmentioning
confidence: 87%
“…Gleaning from our past experience with both experiments and simulations of the MH formation process in sandy media [20,23,33], we postulate that the rate of hydrate formation rate (and the corresponding heterogeneity effects on the spatial distribution of SH) can be controlled by the degree of sub-cooling (∆Tsub) applied to the closed system (laboratory apparatus) used in the excess-water method. The term ∆Tsub can be defined as the onset temperature of MH below its equilibrium temperature (Teq).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations